Agronomic performance of cowpea cultivars (Vigna unguiculata (L.) Walp) under application of limestone doses - De Almeida, Antônio Luís Galvão; Mingotte, Fábio Luiz Checchio [UNESP]; Coelho, Anderson Prates [UNESP]; Lemos, Leandro Borges [UNESP]; de Brito Melo, Francisco; de Mello Prado, Renato [UNESP] (Revista Brasileira de Ciencias Agrarias, 2021)
Evaluating agricultural management practices, such as liming, is essential in regions with acidic soils to increase the yield of agricultural crops. The aim was to evaluate soil fertility, agronomic performance, and grain quality of cowpea cultivars under application of limestone doses. The experiment was carried out in Argissolo Vermelho Amarelo (Ultisol), with initial base saturation of 26%, during two agricultural years. A randomized block design was used, in split plots, with four replications. The plots were composed of five limestone doses (0, 1, 2, 3 and 4 times the recommended rate to reach 50% base saturation), and the subplots were formed by two cowpea cultivars (BR 17 Gurgueia and BRS Guariba). The applied doses of limestone, with relative total neutralizing power (RTNP) of 91%, were 0, 1.3, 2.6, 3.9 and 5.2 t ha-1. Liming increased soil fertility, increasing pH, calcium, magnesium, and base saturation, and decreasing soil acidity. Maximum grain yields were obtained with limestone doses between 3.1 and 3.2 t ha-1 for the cultivar BR 17 Gurgueia and between 3.3 and 3.4 t ha-1 for the cultivar BRS Guariba, reaching average base saturation values of approximately 48 and 55%, respectively.
Keywords: Grain yield; Liming; Soil acidity; Yield components